Role of DNA methylation in the chromium tolerance of Scenedesmus acutus (Chlorophyceae) and its impact on the sulfate pathway regulation. (December 2020) - Ferrari, Michele; Torelli, Anna; Marieschi, Matteo; Cozza, Radiana
Graphical abstract: Highlights: Cytosine methylation occurred mainly in the symmetric CG sites in Scenedesmus acutus DNA is differently methylated in the chromium tolerant strain of Scenedesmus acutus The cytosine methylation status impacts on sulfate uptake/assimilation pathway Epigenomic marks the resistance to chromium stress in Scenedesmus acutus Abstract: DNA methylation is a very important epigenetic modification that participates in many biological functions. Although many researches on DNA methylation have been reported in various plant species, few studies have assessed the global DNA methylation pattern in algae. Even more the complex mechanisms by which DNA methylation modulates stress in algae are yet largely unresolved, mainly with respect to heavy metal stress, for which in plants, metal- and species- specific responses were instead evidenced. In this work, we performed a comparative Whole-Genome Bisulfite Sequencing (WGBS) on two strains of the green alga Scenedesmus acutus with different Cr(VI) sensitivity. The pattern of distribution of 5-mC showed significant differences between the two strains concerning both differentially methylated local contexts (CG, CHG and CHH) and Differentially Methylated Regions (DMRs) as well. We also demonstrated that DNA methylation plays an important role in modulating some genes for sulfate uptake/assimilation confirming the involvement of the sulfate pathway in the Cr-tolerance. Our results suggest that DNA methylation may be of particular importance in defining signal specificity associated with Cr-tolerance and in establishing new epigenetic marks which contribute to the adaptation to metal stress and also to transmit the epigenomic traits to the progeny.